RESPON MAHASISWA TERHADAP PEMBELAJARAN GRAMMAR BERBASIS WEBSITE - Hasanah, Henny Uswatun (STAIN PAMEKASAN, 2016)
This research has four research focuses, they are: how is the design of grammar instruction website based at the English teaching learning programme; how does the stage of grammar instruction website based at the English teaching learning programme; what are the obstacles of grammar instruction website based at the English teaching learning programme; and what are the advantages of grammar instruction website based at the English teaching learning programme.The result showed that grammar design of website based has good enough result, but in the stage of arranging learning material, the design of website and evaluating the studentsâ result still difficult especially to control the instruction which is done by the students.Some of learning obstacles are money, the availability of hard and soft ware computer, the limitness of technical and theory knowledge and acceptance of technology.Good preparation and planning can solve the obstacles, that is the significance of grammar instruction website based, they are easy lecturersâ assignment in their learning activities, make the students regularly use the internet as instruction media, studentsâ absence or canât follow the instruction can open the situs of grammar instruction and stay it at home, and the students can study without limited the place and time.